ANALISIS MISKONSEPSI SISWA KELAS VIII PADA MATA PELAJARAN IPA TERPADU DI SMP N 3 KOTA KUPANG TAHUN AJARAN 2018/2019 - agus maramba meha; Yonathan Foeh; Simson Obhetan (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
ABSTRACT This study aims to Analyze misconceptions about biological material from Integrated Science subjects at SMP N 3 Kupang City in the 2018/2019 academic year. The research method used is a qualitative method with a descriptive research design. Data collection to identify and describe misconceptions among students is done by using multiple-choice questions based on diagnostic test techniques that are equipped with Certainty of Response Index (CRI) and interviews. To analyze qualitative data in this study using the formula p = f / n × 100 to find out the percentage of students who experience understanding concepts, misconceptions and not understanding concepts. The data is then reduced, presented, and given a conclusion.Lessons are taken to identify students' misconceptions namely the respiratory system in humans. The test instrument consisted of 10 multiple choice questions and 5 question items that were given to analyze students' misconceptions. Cognitive development of students is very influential on the pattern of understanding of students themselves. This is indicated by the large percentage of students experiencing misconceptions that occur in the realm of application (C3), namely in question no. 7 with total misconceptions reaching 70.97% followed by a question no. 6 with a total of 54.83% and questions number 8 with a total of 45.16%, followed by the realm of understanding (C2) ie in question no. 3 with a percentage of 41.93% and the lowest percentage is in the realm of knowledge (C1) in question no. 15 with a percentage of 19.35%. Misconceptions experienced by students due to students' understanding patterns also vary due to several factors, namely internal factors in the form of student conditions and external, namely the teacher. Keywords: Misconceptions, Diagnostic Tests, student